2019
DOI: 10.1016/j.cub.2019.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Reprogramming of Positional Memory in a Regenerating Appendage

Abstract: Highlights d Genetic screen identifies a mutation (mem, pola2) that disrupts fin regeneration d pola2 inactivation causes a long-lasting reduction in size of new structures d pola2 inactivation alters blastemal proliferation and size d Progenitor cell-cycle interference alters positional memory in several contexts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 56 publications
0
22
1
Order By: Relevance
“…Wound sites and the neighboring tissues act as signaling centers in many regenerating organisms, instructing the re-patterning of body parts or blastema initiation – for example in Hydra polyps ( Chera et al, 2009 ), zebrafish caudal fins ( Wang et al, 2019 ), or planarians ( Oderberg et al, 2017 ; Petersen and Reddien, 2009 ; Reddien and Sánchez Alvarado, 2004 ; Wurtzel et al, 2015 ). We found an analogous correlation between wound site and blastema position, however in Clytia medusa signaling from the wound site is not sufficient to trigger regeneration, but it is likely conditional.…”
Section: Discussionmentioning
confidence: 99%
“…Wound sites and the neighboring tissues act as signaling centers in many regenerating organisms, instructing the re-patterning of body parts or blastema initiation – for example in Hydra polyps ( Chera et al, 2009 ), zebrafish caudal fins ( Wang et al, 2019 ), or planarians ( Oderberg et al, 2017 ; Petersen and Reddien, 2009 ; Reddien and Sánchez Alvarado, 2004 ; Wurtzel et al, 2015 ). We found an analogous correlation between wound site and blastema position, however in Clytia medusa signaling from the wound site is not sufficient to trigger regeneration, but it is likely conditional.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with hydroxyurea, an inhibitor of DNA replication, in the early stages of regeneration (2-5 dpa) results in smaller tails, further supporting a role for cell proliferation (Wang et al, 2019). The source is still unknown, but may include a population of resident stem cells associated with myofibres, termed muscle satellite-like stem cells, dedifferentiated muscle fibers generated as the myosepta near the amputation plane degenerate (Somorjai et al, 2012b), or even coelomocytes.…”
Section: Cephalochordatamentioning
confidence: 98%
“…Treatment with TH throughout regeneration is sufficient to robustly rescue distal identity (Figure 3B). Previous studies have shown that cellular memory within the blastema dictates fin size during regeneration (Tornini et al, 2016; Wang et al, 2019), and we asked if the TH rescue of distal morphology was due to effects of the hormone on the blastema. We treated hypothyroid fish with TH (in the form of T4) for 24 hours during each of the first 3 days post amputation (dpa), but found that none of these treatments were sufficient to rescue distal patterning in regenerates (Figure 3—Figure Supplement 1).…”
Section: Resultsmentioning
confidence: 99%